Areal distribution of rock glaciers in the Argentera Massif (Maritime Alps) as a tools for recent glacial reconstructions. - RIBOLINI, ADRIANO (1999)
The areal distribution of rock glaciers on the Italian side of the Argentera Massif is weakly irregular and clustered. The factors that determine the characteristics of irregularity and clustering are the orographic framework and the presence of areas in which the occurrence, or recent disappearance, of glacial conditions has inhibited the development of the rock glaciers. The sectors of relief that interrupt the continuous presence of the rock glaciers are currently influenced by glacial conditions (Clapier-Maledia-Gelas zone) and by recently extinct glaciation (Argentera zone). In these sectors the rock glaciers are found only at high altitudes (higher than 2.570 m), while on the remaining reliefs of the Massif they are present in various generations from 2.400 m to 2.600 m. In first analysis, the areal distribution of the rock glaciers can contribute to the understandingm of the deglaciation modality of the Argentera Massif.